2011
DOI: 10.1093/scan/nsr008
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the right prefrontal cortex alters moral judgement

Abstract: Humans daily face social situations involving conflicts between competing moral decision. Despite a substantial amount of studies published over the past 10 years, the respective role of emotions and reason, their possible interaction, and their behavioural expression during moral evaluation remains an unresolved issue. A dualistic approach to moral evaluation proposes that the right dorsolateral prefrontal cortex (rDLPFc) controls emotional impulses. However, recent findings raise the possibility that the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 25 publications
7
85
0
1
Order By: Relevance
“…Similar stimulation parameters (i.e., fixed intensity of stimulation, 15 minutes of stimulation) have been used before to suppress activity of prefrontal regions prior to task requiring social judgments (e.g., reciprocal fairness, moral judgments), with the effects of stimulation continuing after the end of the actual stimulation (e.g., Baumgartner, Knoch, Hotz, Eisenegger, & Fehr, 2011;Eisenegger, Treyer, Fehr, & Knoch, 2008;Knoch, Pascual-Leone, Meyer, Treyer, & Fehr, 2006;Tassy et al, 2012). Talairach coordinates (Talairach & Tournoux, 1988) for the dmPFC were x = 1.5, y = 31.5, and z = 35.5; these coordinates were taken from previous neuroimaging work demonstrating an activation of this region during social impression updating (Mende-Siedlecki et al, 2012).…”
Section: Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%
“…Similar stimulation parameters (i.e., fixed intensity of stimulation, 15 minutes of stimulation) have been used before to suppress activity of prefrontal regions prior to task requiring social judgments (e.g., reciprocal fairness, moral judgments), with the effects of stimulation continuing after the end of the actual stimulation (e.g., Baumgartner, Knoch, Hotz, Eisenegger, & Fehr, 2011;Eisenegger, Treyer, Fehr, & Knoch, 2008;Knoch, Pascual-Leone, Meyer, Treyer, & Fehr, 2006;Tassy et al, 2012). Talairach coordinates (Talairach & Tournoux, 1988) for the dmPFC were x = 1.5, y = 31.5, and z = 35.5; these coordinates were taken from previous neuroimaging work demonstrating an activation of this region during social impression updating (Mende-Siedlecki et al, 2012).…”
Section: Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%
“…When measuring rTMS's effects using the "dilemma" scenarios selected from a battery developed by Greene et al [28], LF rTMS over the right DLPFC increased utilitarian responses during objective evaluation of moral dilemmas, compared to a sham group. For the results, the authors suggested that the right DLPFC stimulated by LF rTMS induced participants toward a rational cognitive control process, and integrated emotions caused by contextual information appraisal in moral judgments [72]. Buckholtz et al [9] studied blameworthiness and punishment decisions using LF rTMS over the DLPFC.…”
Section: Decision-makingmentioning
confidence: 99%
“…In summary, in decision-making studies related to emotion, rTMS modulates delayed discounting [13,69], food choice [10], moral judgment [72], and blameworthiness and punishment decisions [9]. In decision-making studies relevant to cognitive functions, rTMS affects visuospatial attention [71], perception [57], object identification [77], spatial working memory [36], function and manipulation tool knowledge [33], and visuomotor tasks [25].…”
Section: Decision-makingmentioning
confidence: 99%
“…• Implicit racial bias -propranolol has been used to virtually abolish implicit racial bias in subjects, without affecting any explicit racial prejudice measures (Terbeck 2012). • Utilitarian Moral Judgment-repetitive TMS disrupting activity in the right dorsolateral prefrontal cortex increases utilitarian moral judgments (Tassy 2012). TMS disruption of the right temporoparietal junction has been shown to lead subjects to pay less attention to actors' mental states and make moral judgments based more on consequences (Young 2010).…”
Section: Types Of Neurointerventionsmentioning
confidence: 99%